2013
DOI: 10.1371/journal.pone.0067324
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Health Benefits and Cost-Effectiveness of 10-Valent and 13-Valent Pneumococcal Conjugate Vaccination in Kenyan Children

Abstract: BackgroundThe GAVI Alliance supported10-valent pneumococcal conjugate vaccine (PCV10) introduction in Kenya. We estimated the cost-effectiveness of introducing either PCV10 or the13-valent vaccine (PCV13) from a societal perspective and explored the incremental impact of including indirect vaccine effects.MethodsThe costs and effects of pneumococcal vaccination among infants born in Kenya in 2010 were assessed using a decision analytic model comparing PCV10 or PCV13, in turn, with no vaccination. Direct vaccin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 28 publications
1
39
0
Order By: Relevance
“…The study was conducted at Kilifi County Hospital (KCH) in a rural area on the Kenyan coast. Haemophilus influenzae type b and pneumococcal conjugate vaccines were introduced in November 2001 and February 2011, respectively . The antenatal HIV prevalence is 4.9% .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study was conducted at Kilifi County Hospital (KCH) in a rural area on the Kenyan coast. Haemophilus influenzae type b and pneumococcal conjugate vaccines were introduced in November 2001 and February 2011, respectively . The antenatal HIV prevalence is 4.9% .…”
Section: Methodsmentioning
confidence: 99%
“…Haemophilus influenzae type b and pneumococcal conjugate vaccines were introduced in November 2001 and February 2011, respectively. 15,16 The antenatal HIV prevalence is 4.9%. 17 KCH provides inpatient and outpatient services for HIV and malnutrition.…”
Section: Study Settingmentioning
confidence: 99%
“…Previous studies either focused on demonstrating the health impact of PCV 4,5,[9][10][11] , or explored how new vaccines affected specific health system functions or vaccination coverage 12,13 . No research has evaluated the effects of adding PCV into EPI nor how it, as one component of the Integrated Global Action Plan for the Prevention and Control of Pneumonia and Diarrhoea 14 , may have affected wider health systems.…”
Section: African Health Sciences Vol 15 Issue 3 September 2015mentioning
confidence: 99%
“…The Streptococcus pneumoniae bacterium is a major cause of pneumonia 2 , and of other illnesses such as meningitis 3 . The effectiveness of pneumococcal conjugate vaccines (PCV) in preventing pneumonia has been established 4,5 and the World Health Organization recommends the adoption of PCV into vaccination programmes in developing countries with high pneumonia mortality rates 6 . With Gavi Alliance…”
Section: Introductionmentioning
confidence: 99%
“…Allegedly, one of the reasons that a Secretary of Health in our country was summarily dismissed from Office was his controversial decision to procure Pneumonia Conjugate Vaccine (PCV) 10 over PCV13. Existing CEA studies showed that both PCV 10 and PCV13 were cost effective based on GDP per capita with PCV 13 moderately more cost-effective [3][4][5][6]. During this time, information about the protective effect of Protein D carrier unique to PCV10 against H. influenzae disease has yet to be explored.…”
mentioning
confidence: 99%